The Consequences of Conspiracy Theories in the Era of COVID-19 - Utpreksha G Gaude (Journal of Clinical and Diagnostic Research, 2021)
The COVID-19 pandemic has overtaken the lives of millions around the world. While this has helped the virtual technology make advances, it has restricted social beings to their households for over a year. It is only natural to want a change from the boring view of the house and the Olympics being conducted itself is one of the global feats that showcase the resilience of people to strive forward without letting the virus command their lives. With frustration predominating the powerful emotions, people are slowly beginning to resign to the acceptance of the dangers of the deadly virus with its constantly evolving nature. The latest delta variant is the most dangerous one so far. Despite the extensive research being carried out by various diligent scientists, the ultimate cure has yet to be found. Until then, our best hope is the vaccination and following the guidelines of social distancing and protection with masks. These are simple, common-sense rules that need the least amount of instruction yet people seem to find it hard to adhere to these new norms. There is increasing hesitancy and fear due to lack of research but if people can be brave enough to weather the perils of the virus at a universal scale, they should be able to brave the tiny prick as well.